2008
DOI: 10.1158/1078-0432.ccr-07-4001
|View full text |Cite
|
Sign up to set email alerts
|

The Acidic Tumor Microenvironment Promotes the Reconversion of Nitrite into Nitric Oxide: Towards a New and Safe Radiosensitizing Strategy

Abstract: Purpose: The biological status of nitrite recently evolved from an inactive end product of nitric oxide catabolism to the largest intravascular and tissue storage of nitric oxide (NO). Although low partial O 2 pressure favors enzymatic reconversion of nitrite into NO, low pH supports a nonenzymatic pathway. Because hypoxia and acidity are characteristics of the tumor microenvironment, we examined whether nitrite injection could preferentially lead to NO production in tumors and influence response to treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 44 publications
(36 reference statements)
2
39
1
Order By: Relevance
“…By contrast, optimal iNOS activation was shown to induce apoptosis and to exert antitumor and antimetastatic effects. Besides, at micromolar concentrations, both NO and its oxidative product nitrite are known to downregulate respiratory mitochondrial functions, in a variety of cells including tumor cells, macrophages, astrocytes, hepatocytes and myocytes (5,10,22). The observed levels of NO/ nitrite production in both EMT-6 tumor cells and RAW 264.7 macrophages after exposure to LPS/IFN-g matched those concentrations.…”
Section: Discussionmentioning
confidence: 59%
“…By contrast, optimal iNOS activation was shown to induce apoptosis and to exert antitumor and antimetastatic effects. Besides, at micromolar concentrations, both NO and its oxidative product nitrite are known to downregulate respiratory mitochondrial functions, in a variety of cells including tumor cells, macrophages, astrocytes, hepatocytes and myocytes (5,10,22). The observed levels of NO/ nitrite production in both EMT-6 tumor cells and RAW 264.7 macrophages after exposure to LPS/IFN-g matched those concentrations.…”
Section: Discussionmentioning
confidence: 59%
“…The characteristic of NO, by driving local vasodilation and increasing perfusion, suggests that it may have therapeutic potential in tumors to allow transient increase in the delivery and efficacy of anti-cancer drugs. Recently Frerart et al has evaluated the effects of nitrite anion therapy on tumor blood flow, oxygenation, and response to radiotherapy [262]. It was found that nitrite selectively induce a transient increase in tumor partial O 2 pressure (pO 2 ), which improved the efficacy of radiotherapy.…”
Section: Sodium Nitrite Therapy and Cancermentioning
confidence: 99%
“…We therefore tested whether the low pH of tumors (on average pH 6.7) could be exploited to generate NO from nitrites selectively in tumors. We observed ex vivo that nitrite-induced vasodilation was more pronounced at pH 6.7 compared to pH 7.4 (Frerart et al, 2008). We also found that the bioactivity of nitrites at low pH encompassed NO-mediated inhibition of tumor cell respiration, which indicates that the robust and transient increase in tumor pO 2 after nitrite delivery to mice is the result of the combination of vasoactive and metabolic responses.…”
Section: S-nitrosylated Hemoglobin and Nitritesmentioning
confidence: 59%
“…We also found that the bioactivity of nitrites at low pH encompassed NO-mediated inhibition of tumor cell respiration, which indicates that the robust and transient increase in tumor pO 2 after nitrite delivery to mice is the result of the combination of vasoactive and metabolic responses. When administered to reach a plasma concentration of 100 µM in mice, nitrites sensitized tumors to radiotherapy (Frerart et al, 2008). Further clinical applications are however confronted to financial issues: clinical trials are now warranted whereas nitrites or their use in cancer therapy can not be patented.…”
Section: S-nitrosylated Hemoglobin and Nitritesmentioning
confidence: 99%